MASSAGE - Saime Sarıoğlu,; Gülay Dinçer, (Archives of Rheumatology, 2003)
Massage is the application of systemic manipulation to the soft tissues of the body to effect the leucomotor, nervous systems, blood circulation and for theurapeutic purposes. The classic manipulations of massage are classified into five groups according to the application and resulting effects: effleurage, petrissage, friction, tapotement and vibration. Shiatsu and acupressure massage methods are based on the Japanese interpretation of the acupuncture theory. The connective tissue massage is based on the effects of the massage on otonom nervous system. The application to encourage lymph flow with using special hand techniques is known as lymphatic drenage. It helps the lymph flow from obstructed to obstructed areas.